Upaya Meningkatkan Promosi Tahu Walik di Kelurahan Rungkut Kidul Melalui Inovasi Branding Produk dari Oemah Djadjan - Muhammad Fajrul Yusuf Bahri; Aufa Izzudin Baihaqi (Yayasan Daarul Huda Kruengmane, 2023)
Indonesia is a developing country and has started the process of improving its economic system. This increase is happening in many fields ranging from economics to politics, from socio-culture to various fields. This increase effort is to support the country's economy to realize the expectations of daily comfort of the Indonesian people and bring Indonesia into the era of globalization. This can be seen from the many new businesses that have begun to form in Indonesia. One important way for entrepreneurs to develop and succeed in their business is to be able to apply the right strategy in running their business. Micro, small and medium enterprises manage a variety of typical food, beverage and handicraft products with the latest innovations in the Rungkut Kidul sub-district of Surabaya City. One example is Tahu Walik, a traditional herbal medicine, woven from Surabaya and the Legendary Spikoe Cake made from unique ingredients. Focusing on unique food, beverages, and crafts alongside the latest innovations, MSMEs will face many challenges in managing their business, including production, packaging, branding, and product marketing. MSMEs selected to be assisted in product development are located on Jalan Raya Rungkut Kidul, Rungkut Kidul sub-district, Rungkut sub-district, Surabaya City, East Java Province. This method of implementing community service activities uses a qualitative approach with the type of observation, recording, and interviews with MSMEs related to various obstacles faced during product marketing. The target group in this activity is MSMEs that have been analyzed by KKNT-MBKM students and the example used is UMKM Tahu Walik